ANALISIS PENGARUH UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - B2043131011, URAY NDARU MUSTIKA (Universitas Tanjungpura, 2019)
ABSTRACTÂ The purpose of research conducted is to test and analyze the influence of firm size and capital structure on profitability and itâ€™s influence on firm value. The design used in this research is descriptive and path analysis. The sample in this research is determined as many as 65 companies. Criteria for determining the population is a company engaged in the Manufacturing Industry listed on the Indonesia Stock Exchange. Sampling is done by purposive sampling, the taking of the subject is not based on strata or random but based on the existence of certain objectives and considerations, among others : is a company engaged in the Manufacturing Industry that always publish a summary of financial performance per year during the period of 2012 - 2016 on www.idx.co.id, and is a company engaged in the Manufacturing Industry that never experienced losses during the period of 2012 - 2016. The results of the research analysis that is as follows : 1) firm size has a positively significant influence on profitability, 2) capital structure has a negatively significant influence on profitability, 3) firm size has a positively significant influence on firm value, 4) capital structure has a positively significant influence on firm value, and 5) profitability has a positively significant influence on firm value.Kata Kunci : Ukuran Perusahaan, Struktur Modal, Profitabilitas, Nilai Perusahaan